The unique deep sea—land connection: interactive 3D visualization and molecular phylogeny of Bathyhedyle boucheti n. sp. (Bathyhedylidae n. fam.)—the first panpulmonate slug from bathyal zones - Timea P. Neusser; Katharina M. Jörger; Eva Lodde-Bensch; Ellen E. Strong; Michael Schrödl (PeerJ, 2016)
The deep sea comprises vast unexplored areas and is expected to conceal significant undescribed invertebrate species diversity. Deep waters may act as a refuge for many relictual groups, including elusive and enigmatic higher taxa, but the evolutionary pathways by which colonization of the deep sea has occurred have scarcely been investigated. Sister group relationships between shallow water and deep sea taxa have been documented in several invertebrate groups, but are unknown between amphibious/terrestrial and deep-sea species. Here we describe in full and interactive 3D morphoanatomical detail the new sea slug species Bathyhedyle boucheti n. sp., dredged from the continental slope off Mozambique. Molecular and morphological analyses reveal that it represents a novel heterobranch gastropod lineage which we establish as the new family Bathyhedylidae. The family is robustly supported as sister to the recently discovered panpulmonate acochlidian family Aitengidae, which comprises amphibious species living along the sea shore as well as fully terrestrial species. This is the first marine-epibenthic representative among hedylopsacean Acochlidiida, the first record of an acochlidian from deep waters and the first documented panpulmonate deep-sea slug. Considering a marine mesopsammic ancestor, the external morphological features of Bathyhedyle n. gen. may be interpreted as independent adaptations to a benthic life style in the deep sea, including the large body size, broad foot and propodial tentacles. Alternatively, the common ancestor of Bathyhedylidae and Aitengidae may have been a macroscopic amphibious or even terrestrial species. We hypothesize that oophagy in the common ancestor of Aitengidae and Bathyhedylidae might explain the impressive ecological and evolutionary flexibility in habitat choice in the Acochlidiida.